2021
DOI: 10.1186/s12877-021-02057-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of potentially inappropriate medication and risk of adverse drug events among older adults with chronic renal insufficiency: a population-wide cohort study

Abstract: Background The use of potentially inappropriate medication (PIM) in population of older adults may result in adverse drug events (ADE) already after short term exposure, especially when it is prescribed to patients with chronic kidney disease (CKD). In order to limit ADE in the treatment of older adults PIM lists have been constructed as a source of information for healthcare professionals. The aim of this study was to estimate the utilization of PIM and incidence of ADE in older adults (≥70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous studies have highlighted the common use of PIMs and renally inappropriate medications among hospitalized older patients with CKD (Tesfaye et al, 2019;Chahine, 2020;Sheikh Rezaei et al, 2021), suggesting a lack of appropriate assessments of medication regimens as kidney function deteriorates; however, no study has previously reported on differences in CKD diagnosis and PIM use among geriatric and nephrological acute care settings. The present study, performed in wards of Geriatrics and Nephrology, aims to assess 1) the prevalence of CKD under-reporting at hospital discharge; 2) the prevalence of inappropriate prescription/dosing of renally excreted drugs at hospital discharge; and 3) factors associated with higher rates of PIMs and CKD under-reporting in the overall population and specific settings.…”
mentioning
confidence: 99%
“…Previous studies have highlighted the common use of PIMs and renally inappropriate medications among hospitalized older patients with CKD (Tesfaye et al, 2019;Chahine, 2020;Sheikh Rezaei et al, 2021), suggesting a lack of appropriate assessments of medication regimens as kidney function deteriorates; however, no study has previously reported on differences in CKD diagnosis and PIM use among geriatric and nephrological acute care settings. The present study, performed in wards of Geriatrics and Nephrology, aims to assess 1) the prevalence of CKD under-reporting at hospital discharge; 2) the prevalence of inappropriate prescription/dosing of renally excreted drugs at hospital discharge; and 3) factors associated with higher rates of PIMs and CKD under-reporting in the overall population and specific settings.…”
mentioning
confidence: 99%
“…The 30 days exposure time window was chosen based on similar studies done on the PIM’s risk. 36 38 The cohorts were matched based on propensity scores and were followed for events of critical care services and deaths until release from isolation ( figure 1 ). This retrospective cohort study was approved by the Seoul National University Institutional Review Board (IRB No.…”
Section: Methodsmentioning
confidence: 99%
“…Substances are listed in different groups according to organs they affect and their chemical, pharmacological and therapeutic characteristics. In Austria each medication has an additional unique Austrian pharmaceutical registration number, which is linked to the ATC-codes [ 32 ]. Patients with antibiotic, antiphlogistic, analgesic, bisphosphate, and corticosteroid prescriptions were identified by ATC codes J01, M01, N01, M05BA and H02 and their subcodes, respectively.…”
Section: Methodsmentioning
confidence: 99%